Twelve new species of Athetis Hübner, [1821] 1816 from China (Lepidoptera, Noctuidae) - Han, H. L.; Kononenko, V. S. (Zootaxa, 2011)
Twelve new species of the genus Athetis Hübner, [1821] 1816 sensu stricto (Noctuidae, Noctuidae, Caradrinini, Athetiina) (A. hoengshana sp. n., A. simplex sp. n., A. orthosioides sp. n., A. eupsilioides sp. n., A. tridentata sp. n., A. linzhi sp. n., A. flavicolor sp. n., A. biserrata sp. n., A. minivalva sp. n., A. longiharpe sp.n., A. bicornuta sp. n., A. furcatula sp. n.) are described from China. All new species are illustrated with imagines, and with male and female genitalia.